Tallow tree allocates contrasting secondary chemicals in response to varying environments along elevational gradients. (3rd April 2020) - Xiao, Li; Zhang, Jialiang; Huang, Wei; Carrillo, Juli; Siemann, Evan; Ding, Jianqing
Abstract: Aims: Understanding how tree species regulate multiple types of secondary chemicals along elevational gradients is critical for elucidating the physiological and ecological strategies of plants in response to varying biotic and/or abiotic environments. This study aims to examine how Chinese tallow tree ( Triadica sebifera ) allocates resources to the production of different secondary chemicals in response to varying environments across elevational gradients. Methods: We conducted field surveys of different herbivore feeding guilds and their damage rates on Chinese tallow trees along an elevational gradient in China and measured secondary chemicals (tannins and flavonoids) in damaged and undamaged leaves. Important Findings: The odds of a leaf being damaged (chewing or scarring) decreased with elevation. Flavonoid concentrations increased with elevation in undamaged leaves but decreased with elevation in damaged leaves, with quercitrin contributing most strongly to this pattern, likely as results of plant responding to changing biotic or abiotic stresses along elevational gradients. Tannin concentrations did not vary with elevation, so undamaged leaves had relatively lower tannin to flavonoid ratios at high elevation than at low elevation. Our study reveals variation in herbivory and contrasting trends in plant secondary metabolism along an elevation gradient and highlights the importance of simultaneously considering multiple types of secondary chemicals in plant physiological and ecological strategies.